Pancreatic Tuberculosis: A Rare Type of Extra Pulmonary Tuberculosis - Dian Daniella (The Indonesian Society for Digestive Endoscopy, 2018)
Tuberculosis is a serious health problem not only in Indonesia, but worldwide. Each year, it occurs in nearly 9.7 million people and claims about 2 million lives worldwide. Pancreatic tuberculosis is a rare type of extra pulmonary tuberculosis that only occur less than 4.7% worldwide. The most common symptoms is abdominal pain and most of the patients shows abdominal tenderness on palpation. Diagnosis of pancreatic tuberculosis consist of tuberculin skin test, ultrasonography, computed tomography-scan, magnetic resonance imaging and biopsy. Diagnosing pancreatic tuberculosis is a challenge because of its rarity and it has similar symptoms as more common pancreatic condition such as pancreatic malignancy. Understanding of pancreatic tuberculosis will increased the clinical awareness that may guide clinicians to avoid unnecessary diagnostic or therapeutic procedures and early diagnosis.